(untitled) (Research, Society and Development, 2024)
Introduction: Unichromatic or "chameleon effect" resins are a new type of material that seeks to achieve tooth-identical coloration with just one resin color, proposing to be a simpler alternative to the layered technique. Objective: The objective of this study is to evaluate whether a national unichromatic composite resin (Vitra Unique - FGM) meets the aesthetic demands related to color in the opinion of different observers. Materials and Methods: The Visual Analog Scale (VAS) and Global Aesthetic Improvement Scale (GAIS) were applied to 60 observers with different levels of knowledge, G1-Patients (N=20), G2-Dental surgeons, (N=20) and G3-Dentistry undergraduates (N=20) immediately after performing Class III and IV restorations with a unichromatic resin in the Integrated Adult Clinic of the undergraduate course of the State University of Maringá(UEM). Results: There was a tendency for all groups to prefer the postoperative period, attributing aesthetic improvement to the restorations performed. Conclusion: The unichromatic resin tested was efficient in mimicking the color of the dental substrate, being a promising alternative for the general practitioner, especially in less complex cases.